2002
DOI: 10.1097/00024382-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Nebulization Attenuates Acute Lung Injury in Sepsis Following Smoke Inhalation in Sheep

Abstract: Pseudomonas pneumonia is a common complication of smoke inhalation injury. Airway casts formed from clotted mucous occur frequently in this condition. A recent report shows that intravenous heparin improves oxygenation and reduces lung damage in a sheep model of smoke inhalation. We hypothesized that nebulized heparin could be an effective means of reducing cast formation. Female sheep (n = 19) were surgically prepared for a study of acute lung injury (ALI). After a tracheotomy, 48 breaths of cotton smoke (<40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 25 publications
4
94
2
1
Order By: Relevance
“…Under light microscopy, magnified digital images were captured using an Olympus BX40 microscope (Olympus Optical, Tokyo, Japan). The Murakami technique, which helps in histological assessment of features, such as edema, congestion, hemorrhage, infiltration of inflammatory cells, and cell proliferation, was employed to grade the degree of lung tissue injury (Murakami et al 2002). Each of these features was graded according to the following scale: 0, absent and appears normal; 1, light or nonsignificant damage; 2, moderate damage; 3, strong damage that may interfere with function; and 4, intense damage that may highly impair or eliminate function.…”
Section: Histological Examinationmentioning
confidence: 99%
“…Under light microscopy, magnified digital images were captured using an Olympus BX40 microscope (Olympus Optical, Tokyo, Japan). The Murakami technique, which helps in histological assessment of features, such as edema, congestion, hemorrhage, infiltration of inflammatory cells, and cell proliferation, was employed to grade the degree of lung tissue injury (Murakami et al 2002). Each of these features was graded according to the following scale: 0, absent and appears normal; 1, light or nonsignificant damage; 2, moderate damage; 3, strong damage that may interfere with function; and 4, intense damage that may highly impair or eliminate function.…”
Section: Histological Examinationmentioning
confidence: 99%
“…However, regulatory agencies and cost may limit the number of animals employed in these studies, which in turn may influence the statistical analysis of the results. The dog model has been utilized to study the delivery of insulin [65] or the treatment of some allergies [66]; monkeys and non-human primates have been employed to assess vaccine delivery [67] or drugs to treat cystic fibrosis [68], where sheep are considered a good model of lung injury [69].…”
Section: Animal Modelsmentioning
confidence: 99%
“…An effect of nebulized heparin on systemic coagulation was reported in one study using a lung injury model (49), but not in studies using pulmonary infection models (36,49) or inhalation trauma models (38)(39)(40)(41)(42). None of these studies, however, showed systemic bleeding.…”
Section: Heparinmentioning
confidence: 97%
“…Nebulized heparin also affected various physiologic parameters and other outcomes, in particular during pulmonary infection (34,35), and inhalation trauma (38)(39)(40)(41)(42)). An effect of nebulized heparin on systemic coagulation was reported in one study using a lung injury model (49), but not in studies using pulmonary infection models (36,49) or inhalation trauma models (38)(39)(40)(41)(42).…”
Section: Heparinmentioning
confidence: 99%